PENGARUH CELEBRITY ENDORSER, BRAND IMAGE DAN PERSEPSI KUALITAS TERHADAP NIAT BELI SEPEDA MOTOR HONDA SCOOPY DI KOTA DENPASAR - Haryantana, I Gede Handre; Ekawati, Ni Wayan (E-Jurnal Manajemen; Vol 4 No 9 (2015), 2015)
The purpose of this study were (1) to determine the influence celebrity endorser influence on purchase intentions Honda Scoopy motorcycle in Denpasar, (2) to determine the effect of brand image influence on purchase intentions Honda Scoopy motorcycle in the city of Denpasar and (3) to determine the effect perceived quality affect the purchase intention Honda Scoopy motorcycle Denpasar.Penelitian City was conducted in Denpasar with a data analysis technique multiple linear regression. The number of samples obtained by using purposive sampling method is a total of 110 respondents. Based on the results of the analysis can be concluded Celebrity endorser, brand image and quality perception positive and significant effect partially on purchase intention Honda Scoopy motorcycle in the city of Denpasar. This indicates that the Celebrity endorser, brand image and perception of quality can increase purchase intention Honda Scoopy motorcycle in Denpasar advice given to manufacturers Honda Scoopy, should the manufacturer Honda Scoopy maintain and pay attention to the quality of Honda Scoopy motorcycle, so that consumer perceptions of quality bicycles Honda Scoopy be better, by doing improvements to minimize the damage to the engine so that the consumer is able to provide an overview on the extent to which the quality of which is owned by Honda Scoopy motorcycle
Keywords: celebrity endorser, brand image, persepsi kualitas, niat beli